PENGARUH EFISIENSI, KEAMANAN, KEMUDAHAN DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN MOBILE BANKING (STUDI PADA NASABAH BCA KABUPATEN TANGERANG): (Studi Pada Nasabah BCA Kabupaten Tangerang) - Galih Ananda Firman; Putri Putri; Nani Yunani; Rika Apriani; Wahyu Wibowo; Karnawi Kamar (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
In this modern era, technology is developing so rapidly, Banking in Indonesia is competing in developing technology, and one of the applications used to conduct banking transactions is mobile banking. This study aims to analyze the effect of efficiency, security, convenience and trust on the interest in using BCA mobile banking and to find out which variables are the most dominant on the interest in using. The analysis method in this study uses primary data, the test stages carried out are: validity test, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, coefficient of determination, F test and T test. The data used in this study used a questionnaire instrument and valid data that was successfully collected as many as 102 respondents. The results of this study indicate that the T count value on the efficiency variable (X1) is 0.715 with a significance value of 0.477. meaning H1 is rejected. So it can be concluded that efficiency (X1) does not affect the interest in using (Y). The T count obtained on the security variable (X2) is -0.146 with a significance value of 0.884. meaning H2 is rejected. So it can be concluded that security (X2) does not affect the interest in using (Y). The T-count value obtained for the convenience variable (X3) is 3.601 with a significance value of 0.001. which means H3 is accepted. So it can be concluded that convenience (X3) affects the interest in using (Y). The T-count value obtained for the trust variable (X4) is 2.981 with a significance value of 0.004. meaning H4 is accepted. So it can be concluded that trust (X4) affects the interest in using (Y). The convenience variable is 0.362 with a significance value of 0.001. This means that the interest in using variable is more dominantly influenced by the convenience variable (X3) compared to other variables.